Analisis Penerapan Restorative Justice sebagai Alternatif Penyelesaian Perkara terhadap Tindak Pidana Pemerkosaan yang dilakukan Anggota Kepolisian - Anes Sefta Asmita (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Restorative Justice is an alternative dispute resolution outside of criminal penalties, in other words, it is resolved through familial means and also aims to repair the relationship between the perpetrator and the victim. Recently, the application of restorative justice has been found in the field, which has become the main basis for resolving criminal cases of rape committed by police officers by filing an appeal in the appellate court, so that the police officer who is the perpetrator of the rape, named Bripda Fauzan (FA), who was previously subjected to the sanction of dishonorable dismissal (PTDH) in the Police Ethics Code Commission session, was not dismissed on the grounds that the rape case was considered resolved after the perpetrator married the victim. However, some time after the appeal decision, the perpetrator was reported again for allegedly neglecting his wife, who is the victim of the rape he married, which will be further examined in this research regarding the cause of Bripda Fauzan (FA) leaving his wife. This study aims to provide a real view of the application of restorative justice as the main basis for resolving rape cases, the method used in this journal is a normative juridical research method with literature studies and looking at empirical facts in the field through news circulating on the Internet media regarding rape cases by police members who are considered to have been completed after marrying the victim. The settlement of rape cases carried out by police members with restorative justice has tarnished the credibility of police institutions that do not seem to understand the fatality of sexual violence cases with the application of restorative justice in cases that have a major impact.